Conceptualizing the Digital Pedagogy in Arts Higher Education: Examining the Roles of Training, Technology Support, and Teacher Mindsets - Tai, Ge; Nasir, Nadia Binti Mohd (South Asian Journal of Social Sciences and Humanities, 2024)
In this concept paper, the propositions for incorporating professional development, ICT awareness, and technical support to introduce technology incorporation practices among College of Arts instructors are discussed. Drawing from past research in practice, this study’s conceptual framework posits value and ability beliefs as the mediators of technology integration practices. This research establishes professional development, ICT knowledge, and technical assistance as determinants of technology integration practices for learning in the study and looks at the value and ability beliefs and their impact on the instructors’ decision to integrate technology into the teaching practice. This work contributes to the generation of practical and theoretical knowledge for designing effective technology integration in arts education practices, underscoring the centrality of the multipronged perspectives of instructors’ belief, content, and practice knowing. In this case, this study seeks to improve the quality of arts education and better prepare College of Arts students for the job market of the still-growing technology focused era by raising the level of preparedness for integrating technology into lessons of the College of Arts instructors.